FINGERPRINT ANALYSIS OF ETHNIC FEMALE KUWAITIS - Kumar, Arunachalam (Journal of Health and Allied Sciences NU, 2011)
Fingerprint patterns and palmar dermatoglyphics have, over the decades not only been of significant application in identity establishment in forensics, but also played an adjunct role in diagnosis and confirmation of quite a few medical afflictions and syndromes.Many data banks on fingerprint profiles covering gender and diverse populations, ethnic groups and occupations have been compiled and are readily available for application and analysis. Observations of oddities, peculiarities or exclusiveness in print patterns across peoples have led to the accumulation of reliable markers that aid diagnostics and in specific assignments based on sex, disease, inheritance (both genotype and phenotype) and in classifications.This paper presents observations on fingerprint patterns and their variations found in adult Kuwaiti females from the Middle-east. A total of 360 prints were collected and results were collated for analysis. The results show a distinct difference in pattern in this ethnic populace, an increased frequency in ulnar loops. This undertaking, to my knowledge, is the first ever to cover a native Arab, could form the nucleus for more such and larger scale studies.
Keywords: dermatoglyphics; dactylography; physical anthropology; ethnicity